Mental Health and Women on Probation or Parole: A Confirmatory Factor Analysis of the Brief Symptom Inventory (BSI-18) - Prost, Stephanie Grace (Women & criminal justice, 2019)
This study examined the robustness of the proposed factor structure of the Brief Symptom Inventory (BSI-18) in a sample of justice-involved women (N = 406). Efforts to assess accurately and intervene effectively regarding mental health issues (namely, somatization, depression, and anxiety) are critical due to growing proportions of women involved in the criminal justice system and the link between mental health and justice-system outcomes among women. Women on probation or parole provided responses to the BSI-18 as part of a larger study on victimization and substance use. Analyses included calculation of descriptive statistics and confirmatory factor and simulation analyses. Results show strong model-data fit indices reflecting that the BSI-18 is a robust and pragmatic self-report symptom inventory for women with criminal justice system involvement. Limitations related to cross-sectional design and a small, nonrandom sample are noted and implications for mental health assessment and intervention are discussed.